Hubungan Rasionalitas Penggunaan Obat terhadap Outcome Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit Cijantung - Putu Wina Widya Artini; Aji Tetuko; Melia Eka Rosita (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease that requires precise therapy to prevent complications, making the rationality of drug use a crucial factor in treatment success. DKI Jakarta has the highest diabetes prevalence in Indonesia, dominated by type 2 at 50.1%, yet research on drug rationality and therapeutic outcomes in type C hospitals remains limited, making Cijantung Hospital a strategic research site. This study aimed to determine the relationship between the rationality of drug use and therapeutic outcomes in type 2 DM patients at Cijantung Hospital. This was a descriptive study using a cross-sectional method with retrospective data collection from medical records for the period of January–December 2025, involving 34 patients who met the inclusion and exclusion criteria. The rationality evaluation showed right indication (100%), right patient (100%), right dose (100%), right route (100%), and right drug (88%), so that overall drug use was categorized as rational (88%). Regarding therapeutic outcomes, 54% of patients achieved the target HbA1c <7% and 24% achieved the target fasting blood glucose (FBG) <130 mg/dL. Fisher’s Exact Test showed no significant relationship between the rationality of drug use and the achievement of either HbA1c (p = 1.000) or FBG (p = 0.574). Drug use at Cijantung Hospital is categorized as rational according to the PERKENI 2021 and 2025 Ministry of Health Regulation standards, but this was not directly correlated with clinical outcomes, which are presumed to be influenced by patient compliance and lifestyle factors.